Synthesis of Thermo-Responsive Hydrogel Stabilizer and Its Impact on the Performance of Ecological Soil - Xiaoyan Zhou; Weihao Zhang; Peng Yuan; Zhao Liu; Jiaqiang Zhao; Yue Gu; Hongqiang Chu (Applied Sciences)
In high-slope substrates, special requirements are imposed on sprayed ecological soil, which needs to exhibit high rheological properties before spraying and rapid curing after spraying. Traditional stabilizers are often unable to meet these demands. This study developed a thermo-responsive hydrogel stabilizer (HSZ) and applied it to ecological soil. The effects of HSZ on the rheological, mechanical, and vegetation performance of ecological soil were investigated, and the mechanism of the responsive carrier in the stabilizer was explored. The experimental results show that the ecological soil containing HSZ has high flowability before response, but its flowability rapidly decreases and consistency sharply increases after response. After the addition of HSZ, the 7 d unconfined compressive strength of the ecological soil reaches 1.55 MPa. The pH value of the ecological soil generally ranges from 6.5 to 8.0, and plant growth in a simulated vegetation box is favorable. Conductivity and viscosity tests demonstrate that the core–shell microcarriers, upon thermal response, release crosslinking components from the carrier, which rapidly react with the precursor solution components to form a curing system. This study provides a novel method for regulating ecological soil using a responsive stabilizer, further expanding its capacity to adapt to various complex scenarios.